Tanggung Gugat Pejabat Pembuat Akta Tanah Terhadap Prinsip Kehati-Hatian Dalam Pembuatan Akta Jual Beli - Moh Bafarirahman Pratama (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
The Deed of Sale Purchase is based on the issue of accounts payable as stated in the Deed of Recognition of Debt, which on the one hand contains the responsibility of Notary in applying the principle of prudence in measuring the legitimacy to make a transition on the guarantee of the certificate made on behalf of the creditor as collateral for the debtor to obtain the receivable. This Deed of Recognition of Debt is reinforced by the agreement payable receivable agreed upon by the parties, which may be followed by the Deed of Sale of Sale as collateral against the debt repayment if the debtor is defaulted. At the end of this paper concluded that: (1) the recognition of the debt with the guarantee of the right to land can be done by selling the power under the Deed of Recognition of Debt with the guarantee of land rights, and this is not contradictory to the legislation, and (2) The responsibility of the Notary as the official the general author of authentic deeds attaches to civil liability when making a mistake in carrying out his position, with due regard to aspects of making against the law or wanprestasi.